Antiviral phytocompounds target envelop protein to control Zika virus. (December 2018) - Priya, S.; Kumar, Nachimuthu Senthil; Hemalatha, S.
Graphical abstract: Highlights: 25 phytocompounds from antiviral plants were screened to check whether these phytocompounds can interact with envelope protein of Zika virus. Tannic acid from Terminalia arjuna can prevent ZIKA virus entry. The lead phytocompounds can be tested under In vitro and In vivo conditions to test its efficacy against Zika virus infection. Abstract: Zika virus infection causes serious birth defects, including microcephaly, when expectant mothers are infected during pregnancy. Zika outbreaks have been reported in the Pacific Islands, South America, the Caribbean, Africa and parts of South East Asia. Currently, there is no specific treatment available for Zika virus infection. Hence, the current study is focused to identify natural phytocompounds to control Zika virus from few endemic anti-viral herbs by in silico approach. Molecular interactions, Pharmacokinetic Study, Molecular dynamic simulation and annealing were carried out with the phytocompounds and checked using Lipinski filter. The interactions between the phytocompounds and Envelope protein (PDB id: 5JHM) of Zika virus was assessed with SYBYL-X 1.3. The results showed that tannic acid from Terminalia arjuna had better interaction, total score, CScore (6.792 and 5) and formed more number of Hydrogen bonds within 2.5 Å bond length, best activity in pharmacokinetic study, Molecular dynamic simulation and annealing temperature at 310 K. Our results suggested that tannic acid can be utilized as lead candidate to control Zika virus infection.